KAJIAN KUALITAS AIR SUMUR SEBAGAI SUMBER AIR MINUM DI KELURAHAN GUBUG KECAMATAN GUBUG KABUPATEN GROBOGAN - Aqnes Budiarti; Rupmini Rupmini; Henna Rya Soenoko (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2013)
ABSTRACT Most of Grobogan people use well water facilities to fulfill water requirement every day. This study aim to evaluate well water quality that used as water drinking resourses in Gubug Grobogan and to determine well water meet the requirement as Regulation of Health Minister No. 416/Menkes/Per/IX/1990. This study is non-experimental research with descriptive analysis. Parameter of water quality that investigated comprised physical parameter, chemical parameter and microbiological parameter. Sample have been taken by simple random sampling from three types of well in Gubug, that is well near the garbage disposal, well near the Gubug village river which all along the river there are tofu factory "Bintang Timur" and syrup factory "Kartika", and well which were far from garbage disposal and gubug village river. Samples were determined by atomic absorption spectrofotometry for cadmium parameter dan spectrofotometry for chromium parameter, and double tube multiplied method for microbiologycal parameter. Physical parameter were analysed by colorimetry, termometry, turbidimetry and TDS meter. The results showed that well water quality in Gubug Grobogan based on physical parameter have appropiated with standard but well near the Gubug village river have not appropiated with colour standard. Based on chemical parameter, the three type of well have appropiated with standard for cadmium and chromium concentration. While based on mikrobiologycal parameter Coliform total have not appropiated with standard.Key words : quality study, well water, water drinking